Do Behavioral Biases Adversely Affect the Macro-economy? - Korniotis, George M.; Kumar, Alok (Review of Financial Studies, 2011)
We investigate whether the adverse effects of investors' behavioral biases extend beyond the domain of financial markets to the broad macro-economy. Focusing on the income risk-sharing role of financial markets, we find that risk sharing is higher (more than double) in U.S. states where investors are more sophisticated and exhibit weaker behavioral biases. The potential for risk sharing varies geographically, but states with better risk-sharing opportunities are able to achieve higher levels of risk sharing only when investors in those states are more sophisticated. Collectively, these results indicate that investors' aggregate behavioral biases and their lack of financial sophistication adversely affect the local macro-economy. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.